Integrated Antennas and Active Beamformers Technology for mm-Wave Phased-Array Systems - Biglarbegian, Behzad (University of Waterloo, 2012)
In this thesis, based on the indoor channel measurements and ray-tracing modeling for the indoor mm-wave wireless communications, the challenges of the design of the radio in this band is studied. Considering the recently developed standards such as IEEE 802.15.3c, ECMA and WiGig at 60 GHz, the link budget of the system design for different classes of operation is done and the requirement for the antenna and other RF sections are extracted. Based on radiation characteristics of mm-wave and the fundamental limits of low-cost Silicon technology, it is shown that phased-array is the ultimate solution for the radio and physical layer of the mobile millimeter wave multi-Gb/s wireless networks. Different phased-array configurations are studied and a low-cost single-receiver array architecture with RF phase-shifting is proposed. A systematic approach to the analysis of the overall noise-figure of the proposed architecture is presented and the component technical requirements are derived for the system level specifications. The proposed on-chip antennas and antenna-in-packages for various applications are designed and verified by the measurement results. The design of patch antennas on the low-cost RT/Duroid substrate and the slot antennas on the IPD technologies as well as the compact on-chip slot DRA antenna are explained in the antenna design section. The design of reflective-type phase shifters in CMOS and MEMS technologies is explained. Finally, the design details of two developed 60 GHz integrated phased-arrays in CMOS technology are discussed. Front-end circuit blocks such as LNA, continuous passive reflective-type phase shifters, power combiner and variable gain amplifiers are investigated, designed and developed for a 60 GHz phased-array radio in CMOS technology. In the first design, the two-element CMOS phased-array front-ends based on passive phase shifting architecture is proposed and developed. In the second phased-array, the recently developed on-chip dielectric resonator antenna in our group in lower frequency is scaled and integrated with the front-end.
Keywords: CMOS; phased array; integrated circuits; receiver front-end; mm-wave; 60 GHz; millimeter-wave; Electrical and Computer Engineering